All Days 2011
DOI: 10.4043/21621-ms
|View full text |Cite
|
Sign up to set email alerts
|

Improved Concentric Thread Connectors for SCRs and Pipelines

Abstract: Concentric thread mechanical connectors have been developed and qualified to ISO 21329 for offshore pipelines and risers. The connector design consists of a conical box and pin with interlocking concentric grooves and redundant metal-to-metal seals. Instead of make-up by screwing, it is designed to "snap" together under simultaneous axial clamping and hydraulic pressure in the thread annulus. After make-up, the connector cannot unscrew, back-off or loosen under dynamic loading and/or thermal cycling. Concentri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A critical zone in the snap-fit connector is the nib groove, which acts as a redundant metal-to-metal seal. As can be seen in Figure 4a, the groove reduces the wall thickness at this region and hence (Pollack and Riggs, 2011).…”
Section: Nib Groovementioning
confidence: 82%
See 2 more Smart Citations
“…A critical zone in the snap-fit connector is the nib groove, which acts as a redundant metal-to-metal seal. As can be seen in Figure 4a, the groove reduces the wall thickness at this region and hence (Pollack and Riggs, 2011).…”
Section: Nib Groovementioning
confidence: 82%
“…In view of this, research into these joint types would be expedited by gaining full understanding into the joint setup, geometrical improvements and , its limitations. So far with recent developments, the most publicly utilized sub-categories for the hydraulically assisted clamped joints remain the push-fit and snap-fit connectors (Verbeck and Holland, 2010, Pollack and Riggs, 2011, OSI, 2013. Both sub-categories achieve the joining of pipelines by some means of radial-interference and surface friction and as such its integrity is largely dependent on surface preparation.…”
Section: Threaded and Coupled Connectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…revealed that the use of SRG and BB in a standard NC46 and NC50 connector indeed had advantages in reducing the stress concentration in T&C connector under axial, bending and torsion loads. No doubt the adaptation of stress relief grooves into the design of T&C connectors has been welcomed and its effectiveness in prolonging connector life established (Pallini et al 2002) (Pollack and Riggs 2011). (API-RP-7G 1998) draws conclusions via experimental fatigue testing under service conditions that an optimal stress reduction can be achieved in an NC50 connection with a relief groove width of approximately 1-inch.…”
Section: Trends In Connector Improvementmentioning
confidence: 99%
“…The use of high strength SCR sections mechanically connected (concept similar to TLP tendons Merlin connector) should be looked into to reduce installation time required by welded connections [18]. An assessment of key riser components: flex joints, stress joints, VIV strakes and buoyancy modules, is recommended to identify qualification required to ensure they are project ready.…”
Section: Riser System Assessmentmentioning
confidence: 99%